Research Trend of Socio Scientific Issues on Chemical Kinetic Materials: Literature Review - Radjawaly Usman Rery; Tri Padila Rahmasari (AL-ISHLAH: Jurnal Pendidikan, 2023)
An individual's success in the 21st century can be measured by their ability to utilise knowledge to enhance their personal qualities. This development can be initiated by enhancing fundamental scientific knowledge. The objective of this study is to examine the correlation between research advancements and socioscientific difficulties in the field of chemistry, with the purpose of aiding advanced researchers in identifying new cutting-edge research topics.  This literature evaluation includes 20 selected articles based on specific inclusion criteria: 1) past five years (2018-2020). 2) accredited by SINTA and indexed at Scopus. 3) Research opportunities in Indonesia 4) Keyword: Journal on socio-scientific issues and reaction rates.  Academic journals can be discovered by utilising the search engine "Publish or Perish." The Socio Scientific Issue (SSI) technique is predominantly used to assess science literature among secondary students. The content of socio-scientific concerns reveals minimum controversion of alcohol associated with the reaction order idea. Delivering this issue will add information and modify the behavior of students in response to the spread of the issue. The outcome of this study may be utilised as a review of the study. The measuring component still minimalizes done is awarness of environment as the result of the SSI approach.